A Brønsted acidic, ionic liquid containing, heteropolyacid functionalized polysiloxane network as a highly selective catalyst for the esterification of dicarboxylic acids. Issue 14 (1st July 2020) - Rajabi, Fatemeh; Wilhelm, Christian; Thiel, Werner R.
Abstract : A novel acidic solid catalyst allows the monoesterification of a series of dicarboxylic acids with high selectivities. Abstract : A Brønsted acidic, ionic liquid containing, heteropolyanion functionalized polysiloxane network was formed by self-condensation of dodecatungstophosphoric acid and a zwitterionic organosilane precursor containing both imidazolinium and sulfonate groups. The resulting hybrid material POS-HPA-IL was investigated as a catalyst for the selective esterification of dicarboxylic acids.